2013
DOI: 10.1038/bmt.2013.71
|View full text |Cite
|
Sign up to set email alerts
|

Duration of first remission, hematopoietic cell transplantation-specific comorbidity index and patient age predict survival of patients with AML transplanted in second CR

Abstract: Allo-SCT is potentially curative for patients with AML. Patients transplanted in CR2 tend to experience inferior survival compared with those in CR1. We retrospectively investigated the impact of pretransplant variables on the outcome of patients transplanted with AML in CR2. Ninety-four patients with AML in CR2 received a transplant between 1999 and 2011 with myeloablative (MA, n ¼ 65) or reduced-intensity conditioning regimens (RIC, n ¼ 29). Variables investigated included cytogenetic risk at diagnosis (SWOG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 29 publications
(30 reference statements)
2
47
0
Order By: Relevance
“…Age groups were dichotomized at ⩾ 55 years, duration of CR1 at ⩾ 6 months and HCT-CI 0-3 or more. Distribution of patients into risk groups as defined by Michelis et al 6 was documented for both the original single-center and the multicenter cohort. Contingency statistics were used to compare the distribution of patient characteristics between the two cohorts.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Age groups were dichotomized at ⩾ 55 years, duration of CR1 at ⩾ 6 months and HCT-CI 0-3 or more. Distribution of patients into risk groups as defined by Michelis et al 6 was documented for both the original single-center and the multicenter cohort. Contingency statistics were used to compare the distribution of patient characteristics between the two cohorts.…”
mentioning
confidence: 99%
“…Data from the original study were used to compare the distribution of variables and outcomes with the multicenter cohort. The collection of data focused on the three prognostic parameters previously identified in the single-center study: 6 patient age at transplant, duration of CR1, HCT-CI, as well as donor type, conditioning regimen intensity, duration of follow-up and survival status. Cytogenetics at diagnosis were not evaluated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Barba et al reported that a flexible HCT-CI was more useful than original HCT-CI for predicting the outcome of such patients [9]. In addition, Michelis et al reported that patients with an HCT-CI of 0-3 had better overall survival [5], but this was a different cut-off value from the original one. These two reports suggested that altering the cut-off value could improve the validity of the HCT-CI.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PAM score is a global risk assessment score including variable factors of comorbidity, condition of transplantation, and disease risk. The usefulness of these risk assessment scores has been validated by some previous studies [3][4][5][6][7][8][9][10][11][12][13], but the scores failed to predict mortality in other reports [14][15][16].…”
Section: Introductionmentioning
confidence: 94%